SIKAP MODERASI BERAGAMA MELALUI EXPERIENTAL LEARNING MAHASISWA LINTAS IMAN DI MADRASAH IBTIDA’IYAH DARUT TAQWA - Rahma, Syerli; Yusuf, Achmad; Fachrudin Yusuf, Wiwin; Muhammada, Muhammada (Jurnal Muara Pendidikan, 2024)
Social conflicts between religions continue to emerge in society, becoming a hot topic in every corner of the country. Many of these highlights have linked the world of education, which should produce a golden generation and high levels of moderation, to turning into a factory producing the seeds of religious blasphemy, terrorism, and suicide bombings. In this case, the most effective and efficient means to ward off these problems is to develop an attitude of religious moderation among the surrounding community. The purpose of this study is to describe experiential learning in the context of creating an attitude of religious moderation at MI Darut Taqwa Pasuruan. This study employs a qualitative approach by using a descriptive method that integrates parsipatif observations, wawancara, and documentation to gather data from teachers, students, and dormitory administrators. The findings of this research highlight the process of forming an attitude of religious moderation through experiential learning at MI Darut Taqwa Pasuruan with interfaith students contributes well; the attitude of religious moderation in madrasas is carried out through daily habits and has positive values ​​that can be applied in forming a moderate attitude among students who in accordance with the practice of the Qur’an and Hadist.